The role of police officers in handling criminal acts through the concept of restorative justice - M Dawud Rizkyandi; Rodliyah Rodliyah; Rina Rohayu H (Institute Of computer Science (IOCS), 2024)
The police are one of the functions of state government in the field of maintaining security and public order, enforcing the law, as well as providing protection, guidance and community services in the context of maintaining domestic security. focuses more on enforcing criminal law on proving the guilt of criminals, focusing more on the consequences of a criminal act, while the causes of criminal acts are seen more as facts or evidence of criminal acts rather than as the root of the problem which should be a concern for losses and recovery for victims of the crime. Criminal law, the National Police through the Republic of Indonesia Police Chief Regulation Number 8 of 2021 concerning handling criminal acts based on restorative justice, provides space for investigators and assistant investigators to implement restorative justice where Litigation is the last resort in handling criminal acts. the concept of restorative justice can embrace the interests of all parties in conflict, this research aims to determine the role of police officers in handling criminal acts through the concept of restorative justice, the research uses normative research methods, namely research that in its study refers to and is based on norms and rules. legal rules, applicable laws and regulations, and other literature materials relevant to the research topic. The collection of legal materials was carried out by means of a literature study, namely through a study of police regulations regarding restorative justice, so that it could be concluded that police restorative justice is a progressive law that sets aside the retributive justice that has been applied so far, as well as mediation efforts for criminal acts that give rise to social conflict or criminal acts. Other penalties can be applied according to the elements specified in the political regulation on restorative justice.